Mental health and wellbeing outcomes of youth participation: A scoping review protocol. - Marlee Bower; Amarina Donohoe-Bales; Andre Quan Ho Nguyen; Scarlett Smout; Julia Boyle; Emma Barrett; Stephanie R Partridge; Mariam Mandoh; Magenta Simmons; Radhika Valanju; Fulin Yan; Cheryl Ou; et al. (PLoS ONE, 2023)
There is growing recognition that young people should be given opportunities to participate in the decisions that affect their lives, such as advisory groups, representative councils, advocacy or activism. Positive youth development theory and sociopolitical development theory propose pathways through which youth participation can influence mental health and wellbeing outcomes. However, there is limited empirical research synthesising the impact of participation on youth mental health and/or wellbeing, or the characteristics of activities that are associated with better or worse mental health and/or wellbeing outcomes. This scoping review seeks to address this gap by investigating the scope and nature of evidence detailing how youth participation initiatives can influence mental health and/or wellbeing outcomes for participants. To be eligible, literature must describe youth (aged 15-24) in participation activities and the impact of this engagement on participant mental health and/or wellbeing outcomes. A systematic scoping review of peer-reviewed and grey literature will be conducted using Scopus, PsycINFO, Embase, Medline and grey literature databases. The scoping review will apply established methodology by Arksey and O'Malley, Levac and colleagues and the Joanna Briggs Institute. Title, abstract, and full text screening will be completed by two reviewers, data will be extracted by one reviewer. Findings will be reported in accordance with the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR), including a qualitative summary of the characteristics of youth participation and their influence on youth mental health outcomes. Youth advisory group members will be invited to deliver governance on the project from the outset; participate in, and contribute to, all stages of the review process; reflect on their own experiences of participation; and co-author the resulting publication. This scoping review will provide essential knowledge on how participation activities can be better designed to maximise beneficial psychosocial outcomes for involved youth.